2008
DOI: 10.1007/s10286-008-0490-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of body mass index on cerebral blood flow velocity

Abstract: Objective-Obesity is a risk factor for cerebrovascular disease. We aimed to determine the effects of high body mass index (BMI) on cerebral blood flow regulation in patients with type-2 diabetes mellitus, hypertension, and stroke.Methods-We analyzed data from 90 controls, 30 diabetics, 45 hypertensives, and 32 ischemic stroke patients who underwent transcranial Doppler for evaluation of blood flow velocities (BFV) in the middle cerebral arteries (MCA) and cerebrovascular resistance (CVR) during supine rest and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 30 publications
6
59
2
Order By: Relevance
“…Multiple imaging modalities corroborate the relationship between vascular risk factors and deficits in resting cerebral blood flow (CBF) (Claus et al, 1996;Novak et al, 2006;Selim et al, 2008;Beason-Held et al, 2007). Similarly, atherosclerosis risk factors impair vascular response to hypercapnia (Groschel et al, 2007;Settakis et al, 2003), as evidenced by Doppler studies.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Multiple imaging modalities corroborate the relationship between vascular risk factors and deficits in resting cerebral blood flow (CBF) (Claus et al, 1996;Novak et al, 2006;Selim et al, 2008;Beason-Held et al, 2007). Similarly, atherosclerosis risk factors impair vascular response to hypercapnia (Groschel et al, 2007;Settakis et al, 2003), as evidenced by Doppler studies.…”
Section: Introductionmentioning
confidence: 84%
“…Although many reports substantiate the link between risks for atherosclerosis and blood flow at a global cerebral or lobar level (Claus et al, 1996;Novak et al, 2006;Selim et al, 2008;Groschel et al, 2007;Settakis et al, 2003), there is only a limited information about the influence of these factors on CBF in structures directly related to memory function. Hippocampus is a major anatomical substrate of memory (Eichenbaum, 2004;Shapiro, 2001), and its structural and functional abnormalities predict Alzheimer's disease (AD) (Glodzik-Sobanska et al, 2005;Mosconi, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis showed that children and adolescents with obesity had cognitive deficits that were most prominent for executive functions 103. This may be explained by decreased levels of CBF in predominantly prefrontal brain areas 104 105. Therefore, physical exercise may provide a promising intervention for executive function deficits of children with obesity, possibly by prolonged enhancement of CBF in the frontal brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effects of obesity on the cerebral vasculature are striking, with several studies showing that obese patients, or patients with an elevated body mass index (BMI), have reduced cerebral blood flow [13]. Here we will describe some potential mechanisms and possible ramifications of reduced cerebral perfusion in obesity.…”
Section: Introductionmentioning
confidence: 99%